I Am Golden - Chen, Eva, 1980-; Diao, Sophie (New York : Feiwel and Friends, 2022)
"[Presents] a moving ode to the immigrant experience, as well as a manifesto of self-love for Chinese American children."--
Keywords: Self-esteem -- Juvenile fiction; Chinese American children -- Juvenile fiction; Chinese American families -- Juvenile fiction; Picture books for children; Self-esteem -- Fiction; Chinese American children -- Fiction; Chinese American families -- Fiction; Picture books